백내장 수술 후 맥락막 두께 변화와 굴절력 오차 - 노현철(Hyun Cheol Roh), 박철용(Choul Yong Park), 오종현(Jong Hyun Oh) (Daihan angwa haghoi jabji, 2016)
목적: 백내장 수술이 맥락막 두께에 미치는 영향을 알아보고 맥락막 두께 변화와 술 후 굴절력 오차와의 관련성에 대해 조사하고자 하였다. 대상과 방법: 2012년 3월부터 2014년 2월까지 수정체유화술 및 인공수정체삽입술을 받은 47명 47안을 후향적으로 조사하였다. 술 전 또는 술 후 1개월, 3개월, 6개월에 시행한 스펙트럼영역 빛간섭단층촬영 사진을 이용하여 중심와아래 맥락막 두께를 측정하였다. 또한 목표굴절력과 술 후 1개월, 3개월, 6개월에 측정한 구면렌즈대응치와의 차이, 매 방문 시에 안압, 중심황반두께 등도 조사하였다. 결과: 중심와아래 맥락막 두께는 술 전보다 술 후 1개월에 평균 5.9 ± 13.3 μm, 술 후 3개월에 평균 7.6 ± 18.1 μm만큼 유의하게 증가하였으나(p=0.004 and p=0.006, respectively), 술 후 6개월에는 유의한 차이를 보이지 않았다(p=0.104). 중심와아래 맥락막두께의 변화량은 술 후 구면렌즈대응치와 술 전 목표굴절력과의 차이값과 술 후 1개월, 술 후 6개월에는 유의한 상관관계를 보이지 않았으나, 술 후 3개월에는 유의한 양의 상관관계를 보였다(r=0.310, p=0.034). 중심와아래 맥락막 두께의 변화량은 안압 변화량, 중심황반두께 변화량과는 유의한 상관관계를 보이지 않았다. 결론: 백내장 수술은 술 후 3개월까지 중심와아래 맥락막 두께를 증가시켰다. 중심와아래 맥락막 두께의 변화는 술 후 굴절력에 영향을 미칠 수 있을 것이다. Purpose: To evaluate the effect of cataract surgery on subfoveal choroidal thickness (SCT) and investigate the relationship between the variation of SCT and refractive error. Methods: We retrospectively reviewed the medical records of 47 patients (47 eyes) who underwent uneventful phacoemulsification cataract surgery from March 2012 to February 2014. SCTs were measured using spectral-domain optical coherence tomography performed before surgery and at 1 month, 3 months and 6 months postoperatively. We investigated the differences in target refraction (TR) and postoperative spherical equivalent (SE), intraocular pressure (IOP) and central macular thickness (CMT) at all follow-ups. Results: Compared with preoperative measurements, SCT showed a significant increase of 5.9 ± 13.3 μm at postoperative 1 month and 7.6 ± 18.1 μm at postoperative 3 months (p = 0.004 and p = 0.006, respectively), but no significant differences at postoperative 6 months (p = 0.104). The correlation between the variation of SCT and the differences in postoperative SE and TR were not significant at 1 month and 6 months, but were positively significant at 3 months (r = 0.310, p = 0.034). The variation of SCT showed no significant correlations with the postoperative change in IOP and CMT. Conclusions: SCT significantly increased up to 3 months after cataract surgery. The variation of SCT may affect the postoperative refractive error. KCI Citation Count: 0